Implementation of a Molecular Tumor Board: The Impact on Treatment Decisions for 35 Patients Evaluated at Dartmouth‐Hitchcock Medical Center. (23rd July 2015) - Tafe, Laura J.; Gorlov, Ivan P.; de Abreu, Francine B.; Lefferts, Joel A.; Liu, Xiaoying; Pettus, Jason R.; Marotti, Jonathan D.; Bloch, Kasia J.; Memoli, Vincent A.; Suriawinata, Arief A.; Dragnev, Konstantin H.; Fadul, Camilo E.; et al.
Abstract : Background: Although genetic profiling of tumors is a potentially powerful tool to predict drug sensitivity and resistance, its routine use has been limited because clinicians are often unfamiliar with interpretation and incorporation of the information into practice. We established a Molecular Tumor Board (MTB) to interpret individual patients' tumor genetic profiles and provide treatment recommendations. Patients and Methods: DNA from tumor specimens was sequenced in a Clinical Laboratory Improvement Amendments‐certified laboratory to identify coding mutations in a 50‐gene panel ( n = 34) or a 255‐gene panel ( n = 1). Cases were evaluated by a multidisciplinary MTB that included pathologists, oncologists, hematologists, basic scientists, and genetic counselors. Results: During the first year, 35 cases were evaluated by the MTB, with 32 presented for recommendations on targeted therapies, and 3 referred for potential germline mutations. In 56.3% of cases, MTB recommended treatment with a targeted agent based on evaluation of tumor genetic profile and treatment history. Four patients (12.5%) were subsequently treated with a MTB‐recommended targeted therapy; 3 of the 4 patients remain on therapy, 2 of whom experienced clinical benefit lasting >10 months. Conclusion: For the majority of cases evaluated, the MTB was able to provide treatment recommendations based on targetable genetic alterations. The most common reasons that MTB‐recommended therapy was not administered stemmed from patient preferences and genetic profiling at either very early or very late stages of disease; lack of drug access was rarely encountered. Increasing awareness of molecular profiling and targeted therapies by both clinicians and patients will improve acceptance and adherence to treatments that could significantly improve outcomes. Implications for Practice: Case evaluation by a multidisciplinary Molecular Tumor Board (MTB) is critical to benefit from individualized genetic data and maximize clinical impact. MTB recommendations shaped treatment options for the majority of cases evaluated. In the few patients treated with MTB‐recommended therapy, disease outcomes were positive and support genetically informed treatment. Abstract : A Molecular Tumor Board (MTB) was established to interpret individual patients' tumor genetic profiles and provide treatment recommendations. For the majority of cases evaluated in its first year, the MTB was able to provide treatment recommendations based on targetable genetic alterations. Increasing awareness of molecular profiling and targeted therapies by both clinicians and patients will improve acceptance and adherence to treatments that could significantly improve outcomes.